1966
DOI: 10.1113/jphysiol.1966.sp007831
|View full text |Cite
|
Sign up to set email alerts
|

The oxygen consumption of the placenta and foetal membranes in the sheep

Abstract: SUMMARY1. In anaesthetized sheep near term the 02 uptake of the foetus from the placenta was reduced to zero either by replacing the foetus with a mechanical pump, or by ventilation of the foetus after delivery or in utero. When umbilical arterial and venous Po. were made equal, they were much less than maternal arterial Po2.2. This difference in Po2 was attributed to 02 consumption both within the placental cotyledons and the extra-cotyledonary foetal membranes. 3. The foetal membranes and cord in the sheep a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
1

Year Published

1967
1967
2008
2008

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(26 citation statements)
references
References 27 publications
5
20
1
Order By: Relevance
“…Thus foetal hypoxia occurs only after a marked reduction in the maternal arterial blood Po2 and attempts to raise the foetal Po2 have met with little success despite the administration of pure oxygen to the mother (Comline, Silver & Silver, 1965;Kirschbaum, Lucas, De Haven & Assail, 1967; Acheson, Cook & Reynolds, 1967;Parker & Purves, 1967). The Po2 gradient across the placenta is still present even when the foetus is supplied with oxygen by other means (Campbell, Dawes, Fishman, Hyman & James, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…Thus foetal hypoxia occurs only after a marked reduction in the maternal arterial blood Po2 and attempts to raise the foetal Po2 have met with little success despite the administration of pure oxygen to the mother (Comline, Silver & Silver, 1965;Kirschbaum, Lucas, De Haven & Assail, 1967; Acheson, Cook & Reynolds, 1967;Parker & Purves, 1967). The Po2 gradient across the placenta is still present even when the foetus is supplied with oxygen by other means (Campbell, Dawes, Fishman, Hyman & James, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…In the 1960's, Campbell et al [69] determined that the PO 2 gradient across the placenta remains constant despite decreases in maternal oxygenation and uterine blood flow. The constant oxygen gradient between maternal and fetal circulation sustains fetal oxygen delivery at normal rates.…”
Section: Placental Oxygen Transfer and Metabolismmentioning
confidence: 99%
“…The fractional distribution ofthe uterine O2 uptake between uteroplacental and fetal tissue can only be determined when the O 2 uptake of one of these two tissues is known. Values reported from in vitro measurements of placental O2 uptake in the sheep, rabbit, rat, mouse, guinea pig, and man range from 100-500 /-tmol.min-'.kg-' (17)(18)(19)(20). However, an in vivo study in the near-term ewe demonstrated the importance of intact uteroplacental and umbilical circulations as well as the absence of anesthesia for normal uteroplacental O2 consumption (12).…”
Section: Resultsmentioning
confidence: 99%